The family on trial in revolutionary France - Desan, Suzanne, 1957- (Studies on the history of society and culture, 2004)
In a groundbreaking book that challenges many assumptions about gender and politics in the French Revolution, Suzanne Desan offers an insightful analysis of the ways the Revolution radically redefined the family and its internal dynamics. She shows how revolutionary politics and laws brought about a social revolution within households and created space for thousands of French women and men to reimagine their most intimate relationships. Families negotiated new social practices, including divorce, the reduction of paternal authority, egalitarian inheritance for sons and daughters alike, and the granting of civil rights to illegitimate children. Contrary to arguments that claim the Revolution bound women within a domestic sphere, The Family on Trial maintains that the new civil laws and gender politics offered many women unexpected opportunities to gain power, property, or independence. The family became a political arena, a practical terrain for creating the Republic in day-to-day life. From 1789, citizens across France-sons and daughters, unhappily married spouses and illegitimate children, pamphleteers and moralists, deputies and judges-all disputed how the family should be reformed to remake the new France. They debated how revolutionary ideals and institutions should transform the emotional bonds, gender dynamics, legal customs, and economic arrangements that structured the family. They asked how to bring the principles of liberty, equality, and regeneration into the home. And as French citizens confronted each other in the home, in court, and in print, they gradually negotiated new domestic practices that balanced Old Regime customs with revolutionary innovations in law and culture. In a narrative that combines national-level analysis with a case study of family contestation in Normandy, Desan explores these struggles to bring politics into households and to envision and put into practice a new set of familial relationships.